Optimization of freeze-thaw durability testing for low-carbon concrete with VPI - Steelandt, Amber (UiT Norges arktiske universitet, 2024)
Concrete, the most widely used building material, significantly impacts the environment, with cement production contributing up to 8% of global CO2 emissions. To address this, low-carbon concrete (LCC) mixes with supplementary cementitious materials (SCMs) have been developed. Fly ash (FA) is a well-established SCM, but with the decline of coal-fired power plants, alternatives like volcanic pozzolans from Iceland (VPI) are needed. This research evaluated the durability of concrete with VPI through freeze-thaw (F-T) resistance, compressive strength, and chloride migration tests. Results showed VPI enhanced long-term strength more than FA, although higher VPI percentages reduced strength. VPI significantly improved chloride migration resistance, with higher percentages yielding greater resistance. Concrete with VPI performed well in F-T tests but generally worse than FA. Different curing methods significantly influenced F-T performance, with the effect dependent on factors such as air percentage, spacing factor, W/B ratio, specific surface area, and pore size distribution.